Analysis of frequency sensitive wind plant penetration effect on load frequency control of hybrid power system. (July 2018) - Aziz, Asma; Oo, Aman Than; Stojcevski, Alex
Highlights: Impact analysis of the non-scheduled wind plant on the frequency regulation. Dynamic dead-band based frequency processor augments WTG frequency controller. 60% of wind plants penetration is a possibility in a strongly interconnected network. Lowest FNadir and fastest settling time make thermal-wind plant as best combination. Abstract: Integration of wind penetration has moved the electricity grid in a transition phase to a new model where wind power plants are expected to participate in all levels of frequency regulation. This paper analyses the load frequency control of hybrid power system consisting of thermal, hydro and gas-based power plants in the presence of non-scheduled wind plants under different operating modes and under different penetration level. A moving average filter and dynamic dead band dependent frequency-active power controller is applied to augment the type-3 wind plant model. Simulation results presented here provides some guidance on the design parameters of frequency regulation scheme in the presence of frequency sensitive wind plant. Simulation results indicate that the penetration level up to 60% of grid code compatible frequency sensitive wind plants participating in the AGC system is a possibility in a strongly interconnected network with low load disturbance. Control area having grid code compatible frequency sensitive wind plant integrated with thermal plant presents better LFC performance than the control area having wind plant combined with gas or hydro power plant. The gas-based power plant model dependency upon fuel limitation and maximum-minimum load limitation highly affects the frequency response and makes them suitable as peak load plant only. A detailed representation of temperature control and maximum rate of fuel valve closing must be included in models to get the proper range of frequency deviations occurring in gas plant based network.